Protein modeling, molecular network and molecular dynamics study of newly sequenced interleukin-18 (IL-18) gene in Mus musculus - Yadav B.S.; Chaturvedi N.; Yadav P.K.; Marina N.; Ganash M.; Barreto G.E.; Ashraf G.M.; Ahmad K.; Baig M.H. (My University, 2025)
Interleukin-18 (IL-18) belongs to the superfamily of IL-1 protein and exerts a pleiotropic pro-inflammatory effect on the body. Generally, this protein is significantly involved in immune defense during infection in cells, but sometimes its anomalous activities produce some inflammatory diseases like rheumatoid arthritis and Crohn’s disease. In the present study, the IL-18 gene was isolated from mice and was subsequently cloned and sequenced. Further, the network analysis was carried out to explore the functional role of IL-18 protein in animals. The 3D protein structure of the IL-18 protein was generated and docked with appropriate 3-([3-cholamidopropyl]dimethylammonio)-1-propanesulfonate (CPS) ligand. Later the complex structure of the protein was subjected to molecular dynamics simulation (MDS) for 50 ns to determine the effect of ligand on protein. The network analysis explored the correlation of IL-18 protein with others proteins and their involvement in the different significant pathway to defend the cell from various diseases. As confirmed by MDS, the CPS:IL-18 complex was found to be highly stable. Our results further indicated that CPS ligand has the potential to act as a drug molecule, in future, for counteracting IL-18 activity. To date, no structural details were available for animal IL-18. Hence, the finding of this study will be useful in broadening the horizon towards a better understanding of the functional and structural aspects of IL-18 in animals. © 2019 Wiley Periodicals, Inc.